PROGRAM âJARI PERIâ UNTUK MENINGKATKAN EFIKASI GURU SD DALAM MENGAJARKAN PREVENSI KEKERASAN SEKSUAL ANAK - , Indah Islawati, Dr. Ira Paramastri, M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Children Sexual Abuse (CSA) is a form of childrenâs rights violation and lead to various adverse effects for children. In order to protect the children, it is necessary to conduct primary prevention to prevent the occurrence of such cases done by the teachers as the agents of CSA prevention. Teachers as agents to prevent CSA need good CSA-prevention teaching efficacy in order for the students to be able to comprehend the topic. This study aims to improve the teachersâ self-efficacy in teaching necessary preventions against CSA to the children. This study will use quantitative research method with The Untreated Control Group Design with Dependent Pretest and Posttest Sample design. The subjects of this research are elementary school teachers chosen purposively. Mixed Anova analysis is used to measure the increase of teachersâ self-efficacy to teach necessary preventions against CSA to the children. Teachersâ self-efficacy to teach necessary preventions against CSA to the children in experiment group higher than control group.